ESG Performance and Ownership Structure on Cost of Capital and Research & Development Investment - Asri Pangestika Lutfiani; Rini Hidayah (LP3M Universitas Putra Bangsa, 2022)
This study aims to determine the effect of ESG performance, institutional ownership, insider ownership, block holder ownership, and foreign ownership on the cost of capital and investment of research and development (R&D). The sample of this study is companies listed on the Indonesia Stock Exchange (BEI) for 2016-2020. The sample selection uses the purposive sampling method and collects through the Thomson Reuters Database and annual report. The results of this study indicate that ESG performance, institutional ownership, and foreign ownership have a negative significant effect on the cost of capital, insider ownership has a positive significant effect on the cost of capital, but block holder ownership does not show a significant relationship to the cost of capital. As for the relationship to research and development investment, only ESG performance, institutional ownership, and foreign ownership have a positive significant effect, the other two types of ownership have a negative and significant effect.